Flouting Maxims Found in Encanto Movie - Fauziah Fauziah; Gaguk Rudianto (Humanitatis : Journal of Language and Literature, 2023)
There are several conditions to create an effective communication, one of them is the utterance of the speaker must be understood by the listener. Utterance can be called as maxim. The speaker can disobey a maxim in purposed as long as the context provides enough indicators for the participant to notice it. This is called flouting maxim. This research discussed about the flouting maxims that found in “Encanto” Movie as data source. The related utterances by characters in the movie were the data of analysis in this research. This research used non-participatory observation as the method of collecting data and categorization based on theory by Grice in Yule (1996) as the method of analyzing data. from analysis of this research can be found there were 15 utterances of flouting maxims found in this Movie. There were 5 utterances of the flouting maxim of quantity, 5 utterances of the flouting maxim of quality, 3 utterances of the flouting maxim of relation, and 2 utterances of the flouting maxim of manner. Finally, the most common flouting maxims found in this movie were maxims of quantity and quality, and the least flouting maxim was maxim of manner.